1995
DOI: 10.1051/jp4:1995871
|View full text |Cite
|
Sign up to set email alerts
|

"Some Features of γ-ε Martensitic Transformation and Shape Memory Effect in Fe-Mn-Si Based alloys"

Abstract: In the present paper several important aspects concerning the shape memory behavior of the z-martensite in the costsavin Fe-Mn-Si-based a110 s and its application are reported. Some einetic features of t K e y-E martensitic transformation are discussed. The effects of the com osition, volume change induced b the transformation, stren th 09 austenite, tem erature of pre ' C s rain on the shape memory e f fect have been inves ! igated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…On the other hand, Andersson et al [11] showed that it is possible to form a large amount of e martensite even when the c has undergone antiferromagnetic transition, as in the case of M S < T N . Gulyaev [12] reported that the addition of Si significantly enhances the yield strength (YS) from 180 MPa for Fe-30Mn to 350 MPa for Fe-30Mn-5.5Si. It is also well known that Si lowers the SFE of the c phase, [13] which favors the formation of e martensite.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Andersson et al [11] showed that it is possible to form a large amount of e martensite even when the c has undergone antiferromagnetic transition, as in the case of M S < T N . Gulyaev [12] reported that the addition of Si significantly enhances the yield strength (YS) from 180 MPa for Fe-30Mn to 350 MPa for Fe-30Mn-5.5Si. It is also well known that Si lowers the SFE of the c phase, [13] which favors the formation of e martensite.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Fe-Mn alloys doped with silicon are of great practical interest. At a certain manganese content (28–33 wt %), the introduction of 4–6 wt % Si to the alloy composition leads not only to the hardening of the alloys [ 18 ] but also facilitates the realization of the shape memory effect [ 17 , 19 , 20 ]. Moreover, the heat treatment of the Fe-30Mn-5Si alloy [ 17 ], which ensured the stabilization of the martensitic structure, made it possible to significantly reduce the martensitic start ( M s ) and finish ( M f ) temperatures: 60 °C and below 60 °C, respectively, in comparison with the Fe-(23-26)Mn-5Si.…”
Section: Introductionmentioning
confidence: 99%
“…NiTi alloys, Cu-based and Fe-based alloys are the most well known types of SMAs. Based on their crystalline structure in the austenitic phase they are grouped in “β-type” with body centered cubic (bcc) cell structure, a subclass of them being Ni-Ti [ 1 ], Co-Ni-Ga [ 2 , 3 , 4 ], Cu-Zn-Al, Cu-Al-Ni [ 5 ] and Ni-Mn-Ga [ 6 , 7 , 8 ], Ni-Fe-Ga Heusler alloys [ 8 , 9 ] and “γ-type”, with face centered cubic (fcc) cell structure, comprising Fe-Mn and Fe-Mn-Si [ 10 , 11 ], FePd [ 12 ] or FeNiCoTi [ 13 ]. Among these, Fe-Mn shape memory alloys present a good workability, weldability, corrosion resistance [ 14 ], large damping effect [ 15 ], recovery strain due to the shape memory effect (SME) [ 16 ] and superelasticity [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that addition of Si atoms enhances reversibility of martensite and the shape memory effect in the Fe-Mn alloys [ 16 ], while the Cr addition (between 5 and 9 wt.%) improves the corrosion resistance of Fe-Mn-Si alloys [ 19 ]. The MT of Fe-Mn-Si alloys shows a particular non-thermoelastic stress-induced γ‒ε martensitic transformation and its ε‒γ reverse transformation during subsequent heating [ 10 , 11 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Additionally, beside ε-martensite (hexagonal close packed—hcp—stress-induced structure), the α’-martensite (body-centred-tetragonal—bct—structure) may appear at the intersections of crystallographic defects induced by plastic deformation such as mechanical twins, stacking faults and shear bands [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%